Serum zinc, copper and iron status of children with coeliac disease on three months of gluten-free diet with or without four weeks of zinc supplements: a randomised controlled trial. (April 2018) - Negi, K; Kumar, R; Sharma, L; Datta, SP; Choudhury, M; Kumar, P
Data about the effect of zinc supplementation with gluten-free diet on normalisation of plasma zinc, copper and iron in patients with coeliac disease are scanty. We evaluated the effect of zinc supplementation on serum zinc, copper and iron levels in patients with coeliac disease, by randomising 71 children newly diagnosed with coeliac disease into two groups: Group A = gluten-free diet (GFD); and Group B = gluten-free diet with zinc supplements (GFD +Zn). The rise in iron and zinc was significantly higher in the latter, but the mean rise of copper levels was slightly higher in the former, but the difference was not significant.